2015
DOI: 10.1111/tpj.13005
|View full text |Cite
|
Sign up to set email alerts
|

A node‐localized transporter OsZIP3 is responsible for the preferential distribution of Zn to developing tissues in rice

Abstract: SUMMARYDeveloping tissues such as meristem with low transpiration require high Zn levels for their active growth, but the molecular mechanisms underlying the preferential distribution to these tissues are poorly understood. We found that a member of the ZIP (ZRT, IRT-like protein), OsZIP3, showed high expression in the nodes of rice (Oryza sativa). Immunostaining revealed that OsZIP3 was localized at the xylem intervening parenchyma cells and xylem transfer cells of the enlarged vascular bundle in both basal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 37 publications
1
104
0
Order By: Relevance
“…(b) Expression of OsHKT1;5 in vasculatures of node I and the basal stem is shown. RNA samples were prepared from enlarged vascular bundles (EBVs) and diffuse vascular bundles (DVBs) of node I using the laser microdissection (LMD; Sasaki et al ., ; Suzuki et al ., ) as well as the basal stem (BS). Relative OsHKT1;5 expression in each part is shown setting its expression in the EVB to 1 ( n = 5–8, ±SD).…”
Section: Resultsmentioning
confidence: 97%
“…(b) Expression of OsHKT1;5 in vasculatures of node I and the basal stem is shown. RNA samples were prepared from enlarged vascular bundles (EBVs) and diffuse vascular bundles (DVBs) of node I using the laser microdissection (LMD; Sasaki et al ., ; Suzuki et al ., ) as well as the basal stem (BS). Relative OsHKT1;5 expression in each part is shown setting its expression in the EVB to 1 ( n = 5–8, ±SD).…”
Section: Resultsmentioning
confidence: 97%
“…Two node‐localized Zn transporters, OsZIP3 and OsHMA2, play pivotal roles in this preferential distribution. OsZIP3 is localized in the marginal region of xylem of EVBs and is responsible for the xylem unloading of Zn at each node (Sasaki et al ., ). OsHMA2 is mainly localized to the phloem of DVBs and is responsible for the phloem re‐loading of Zn (Yamaji et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Initially, it was reported that the cation transporter proteins ZIP1 and ZIP3 might be involved in the uptake of Zn from soil (Ramesh et al, 2003;Bashir et al, 2012). Subsequently, Sasaki et al (2015) observed that OsZIP3 is localized in the nodes, and they further demonstrated that the OsZIP3 protein is responsible for unloading the Zn from the xylem of enlarged vascular bundles in nodes. In addition to these vital candidate genes, 7 of the 29 MTAs were within the intervals of previously mapped QTLs ( Table 3).…”
Section: Gwas Identified Significant Mtas For Biofortificationmentioning
confidence: 99%